Basic Self-Disturbances Related to Reduced Anterior Cingulate Volume in Subjects at Ultra-High Risk for Psychosis - Bonoldi, Ilaria; Allen, Paul; Madeira, Luis; Tognin, Stefania; Bossong, Matthijs G.; Azis, Mathilda; Samson, Carly; Quinn, Beverly; Calem, Maria; Valmaggia, Lucia; Modinos, Gemma; Stone, James; et al. (Frontiers in Psychiatry, 2019)
Introduction: Alterations of the “pre-reflective” sense of first-person perspective (e.g. of the “basic self”) are characteristic features of schizophrenic spectrum disorders and are significantly present in the prodromal phase of psychosis and in subjects at Ultra High Risk for psychosis (UHR). Studies in healthy controls suggest that neurobiological substrate of the basic self involves cortical midline structures, such as the anterior and posterior cingulate cortices. Neuroimaging studies have identified neuroanatomical cortical midline structures abnormalities in schizophrenic spectrum disorders. Objectives: (i) to compare basic self-disturbances levels in UHR subjects and controls (ii) to assess the relationship between basic self-disturbances and alterations in cortical midline structures volume in UHR subjects. Methods: 31 UHR subjects (27 antipsychotic-naïve) and 16 healthy controls were assessed using the 57-item semi-structured Examination of Anomalous Self-Experiences (EASE) interview. All subjects were scanned using Magnetic Resonance Imaging (MRI) at 3T, and grey matter volume was measured in a-priori defined regions of interest (ROIs) in the cortical midline structures. Results: EASE scores were much higher in UHR subjects than controls (p<0.001). The UHR group had smaller anterior cingulate volume than controls (p=0.037). There were no structural brain imaging alterations between UHR individuals with or without self-disturbances. Within the UHR sample, the subgroup with higher EASE scores had smaller anterior cingulate volumes than UHR subjects with lower EASE scores and controls (p= 0.018). In the total sample, anterior cingulate volume was inversely correlated with the EASE score (R=0.52 p<0.016). Conclusions: Basic self-disturbances in UHR subjects appear to be related to reductions in anterior cingulate volume.